Clinical Reasoning: Rare Cause of Hemiparesis and Ataxia in a 36-Year-Old Man. (8th February 2022) - Decker, Jessica; Singh, Mini
Abstract : A 36-year-old left-hand dominant Haitian man presented with a 1-week history of intractable headache, slurred speech, and right facial and hemibody weakness and numbness. In retrospect, he reported episodes of blurred vision, painful oral ulcers, and a nonpruritic rash for 3 years. He was found to have a right retinal hemorrhage on a recent eye examination that was treated with ocular VEGF injections without improvement. On examination, he had oral aphthous ulcers and white papulopustular lesions on the trunk and extremities. His neurologic examination was significant for right-sided facial weakness in an upper motor neuron type pattern, dysarthria, right-sided hemiparesis and hemianesthesia, and right upper extremity ataxia.